Tinjauan Filsafat Ilmu, Konsentrasi Ilmu Komunikasi, Pemikiran Jurgens Habermas, Hans-Georg Gadamer, serta Gary P. Radford - Ludwig Suparmo (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2020)
Abstract This write-up is a literature study on Philosophical Sciences in view of Communications Study. Studying philosophy is a never ending effort. The communication philosophy refers to the ethics theories and guidelines. The most profound of these is the formulation of the dialogic coordinates, a standard set of prerequisite communication elements necessary for inciting dialogue. A short study of three prominent philosophers’, i.e.: Jürgen Habermas, Hans Georg-Gadamer and Gary P. Radford are discussed here as examples to encourage scientific class discussionns.